Government of Tanzania issues guidelines for biofortification to ensure inclusion and scale-up along the value chain - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
Ministry of Agriculture and collaborators prepared guidelines to enable stakeholders to plan, implement and manage various biofortification initiatives from seed variety development to crop production, processing, storage, distribution and consumption.